(untitled) (Fiep Bulletin - online, 2014)
This research was supported by Kohlberg’s Theory of Moral Reasoning Development with the aim of identifying the characteristics of moral development of teenagers who play basketball. The subjects were male athletes from Dom Bosco College’s basketball team aged fifteen to seventeen. A questionnaire was proposed where we rely on Lind’s test: Moral Judment Test and also observation of practices and matches where we could see broadly the relationship between themselves and with their coach, with the sense of victory, honor, virtues learned in the sporting environment and also their ability to make moral choices during the game. After analyzing and interpreting the data it was observed that there was a difference of moral reasoning by age, where older generally had a better moral reasoning then younger, which meets Kohlberg’s theory in relation to social dilemmas. We believe that the team’s ability to resolve conflicts is in agreement with what is proposed by Kohlberg’s theory. The basketball sporting environment may be favoring to the moral development of its practitioners due to the influence of the coach who was quoted as determining to transmit moral values and with this influence he might be able to propouse and develop topics that can be worked as a team in order to increase the team’s process of moral development as well as individually.